2020
DOI: 10.1177/1535370220959747
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlation of human papillomavirus genotypes with clinical factors in cervical samples from Mexican women

Abstract: In the last decade, the inclusion of HPV DNA testing in cervical cancer screening has provided one of the best strategies for the prevention and timely detection of HPV. We conducted a high-throughput HPV genotyping study based on MALDI-TOF mass spectrometry to determine the prevalence of 24 HPV genotypes, including oncogenic genotypes, in Mexican women and correlated the results with cytological findings and clinical variables. We likewise identified the risk factors in patients with the HPV infection. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…These results are comparable with other studies conducted in Mexico. 4 , 28 , 31 , 39 , 40 The genotype distribution pattern showed that the most prevalent combinations were 31-53, 35-53, 53-58, and 33-35. Since these genotypes belong to the α-6 and α-9 species, this could suggest that phylogenetically related HR-HPV genotypes tend to cluster together, in agreement with reports by other authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are comparable with other studies conducted in Mexico. 4 , 28 , 31 , 39 , 40 The genotype distribution pattern showed that the most prevalent combinations were 31-53, 35-53, 53-58, and 33-35. Since these genotypes belong to the α-6 and α-9 species, this could suggest that phylogenetically related HR-HPV genotypes tend to cluster together, in agreement with reports by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…HPV DNA detection and virus load quantification were performed using the Seegene Anyplex™ II HPV 28 system (Seegene, Seoul, Korea), based on a real-time multiplex PCR assay that allows simultaneous amplification, detection, and differentiation of target nucleic acids of 19 high-risk HPV types (16,18,26,31,33,35,35,39,45,45,51,52,53,56,58,59, 66, 68, 69, 73, 82) and 9 low-risk HPV types (6,11,40,42,43,44,54,61,70). 24 This system allowed us to confirm the HPV diagnosis and estimate viral loads by genotype in each patient.…”
Section: Hpv Genotyping and Pathological Examinationmentioning
confidence: 99%
“…En la presente investigación, la mayor frecuencia para alguno de los VPH-AR se presentó en las mujeres que vivían en unión libre 36.6% (48/131) y en las mujeres casadas 33.7% (33/98) (tabla 3). Este patrón es similar a lo reportado por Hernández-Rosas et al (22), en un estudio realizado en mujeres mexicanas, en el que se encontró 15.9% (159/1000) de casos positivos para VPH-AR en las casadas, seguido por 4.5% (45/1000) que respondieron vivir en unión libre. Los resultados obtenidos en la presente investigación no fueron los esperados, ya que se pensaba que las mujeres que tenían pareja estable tendrían menor riesgo de infección por el VPH y que la mayor frecuencia de positividad se detectaría en las mujeres solteras que, por su condición de libertad, podrían tener relaciones casuales o de múltiples parejas y con ello aumentar el riesgo de infección por el VPH.…”
Section: Discussionunclassified
“…The risk factors associated with HPV infection have been widely reported. The more certain factors include sexual behaviors (e.g., number of sexual partners, age at first sexual encounter, and male sex), large number of births, HPV type, and age [15][16][17]. However, the correlation between factors such as smoking, contraceptive methods, HPV viral load and HPV infection remain controversial.…”
Section: Introductionmentioning
confidence: 99%